PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SMA NEGERI 7 KOTA KEDIRI - Setyawan, Sendy; Arifin, Zainal; Surindra, Bayu (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the relationship between learning motivation and learning discipline on economics learning outcomes. The population in this study were students of class X Social Class SMA Negeri 7 Kediri City. The research sample was 30 students taken using purposive sampling technique. Collecting data using questionnaires and documentation techniques. This study uses a quantitative causality research approach. Data analysis used multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results of this study indicate that, 1) partially the motivational variable affects learning outcomes with a value of sig 0.000 < 0.005, 2) partially the discipline variable affects learning outcomes with a value of sig 0.001 < 0.005, 3) the variables of learning motivation and learning discipline in class students X Economic Class subjects SMA Negeri 7 Kediri City simultaneously affect the results with a sig value of 0.000 <0.05. With a coefficient of determination (R Square) of = 0.604 = 60% which is classified as strong.